2018
DOI: 10.3917/mav.103.0137
|View full text |Cite
|
Sign up to set email alerts
|

L’évolution de la comptabilité, du contrôle, de l’audit et de leurs métiers au prisme de la Blockchain : une réflexion prospective

Abstract: Distribution électronique Cairn.info pour Management Prospective Ed.. © Management Prospective Ed.. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
0
7
0
3
Order By: Relevance
“…In a prospective approach, Desplebin et al (2018) illustrated the innovative aspects of blockchain technology that would influence the accounting and audit profession. These authors consider that blockchain will become a "core technology" for the internal control that guarantees the certainty of information for stakeholders: institutions, shareholders, customers, etc.…”
Section: Literature Revuementioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective approach, Desplebin et al (2018) illustrated the innovative aspects of blockchain technology that would influence the accounting and audit profession. These authors consider that blockchain will become a "core technology" for the internal control that guarantees the certainty of information for stakeholders: institutions, shareholders, customers, etc.…”
Section: Literature Revuementioning
confidence: 99%
“…Their study concludes with a series of recommendations to professionals to adapt to this technology and develop their businesses. Desplebin et al (2018) discussed using a prospective approach to the possible consequences of this technology on the accounting and auditing profession. Their study concluded on a series of possible scenarios that could reflect the evolution of the profession in terms of data security, dematerialization of transactions, coordination, and a fair image of accounting information.…”
mentioning
confidence: 99%
“…Blockchain is perceived as a potential source of innovation and major benefits and its development is at the heart of investment policies in many organizations and consortia seeking competitive advantages. The operation of blockchain is carried out in five steps (figure 1, Desplebin et al, 2018). In step 1, agent A registers a written request to agent B in the blockchain's registry (e.g., financial transaction, accounting entry, contract, delivery, transfer of ownership, etc.).…”
Section: What Is Blockchain?mentioning
confidence: 99%
“…It can be thought of as "a very large notebook, which everyone can read freely and without charge, on which everyone can write, but which is impossible to erase and is indestructible" (Delahaye, 2015). Blockchain is characterized by three principles: transparency (information is "public," i.e., shared among users); data protection (no falsification, verification of information by network nodes, no erasure of data, and anonymization); and decentralization (operation without a central trusted actor responsible for administration, control, and more generally, system governance) (Desplebin, Lux, and Petit, 2018). Blockchain has been in the spotlight again recently as new applications are being developed in sectors not directly related to banking or finance, such as logistics and supply chain management (Perboli, Musso, and Rosano, 2018;Kshetri, 2018;Wang and Kogan, 2018;Lesueur, Bironneau, Lux, and Morvan, 2020).…”
Section: What Is Blockchain?mentioning
confidence: 99%
“…An asset can be tangible (car, land) or intangible, such as intellectual property (patent, copyright). Another definition is a technology that allows the registration of transactions that is organized in chronological order and that relies on a distributed network of users via the Internet (Desplebin, Lux, and Petit, 2018). Abreu, Aparicio, and Costa (2018: 1) point out the characteristics making this distributed network so attractive: “This ledger information operates with encrypted data to implement identification, authentication, and authorization of access to information.…”
Section: Background Information and Previous Literaturementioning
confidence: 99%